KAITAN SISTEM OTOMATISASI KANTOR DENGAN PRODUKTIVITAS KERJA - Fadjar - Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2009)
Abstract Program of data processor enable the making and formal correspondences repair and other document. Interview or have conference the long distance can lessen the time journey which castaway to professional manager. Electronic post enable the process quickly to officer needing information which usually require the time days even to be able to until to them. And electronic calendar enable the officer to schedule the meeting- working meeting with as efficient as possible. Keywords : system of office automation, productivity work